Perancangan User Interface pada Aplikasi ‘LiteraLink’ dengan Menggunakan Metode Design Thinking - Lusia Elvira Sue Sare; I Ketut Gede Suhartana (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The level of reading interest among Indonesian people will be 66.7 points in 2023. Increasingly advanced technological developments have led to an increase in the use of digital media, including reading practices which now tend to be digital. Previous research has involved the use of design thinking in creating solutions from a process of empathy for a particular human-centered need. So the design thinking method was used in designing the